Effects of Puerariae Radix extract on the activity of antioxidant - Young-Joon Eun; Ki Rok Kwon; Tae Jin Rhim; Yun-Kyung Song; Hyung-Ho Lim (Korean Pharmacopuncture Institute, 2007)
Objective : The objective of this study was to investigate the antioxidative effects of Puerariae Radix extract. Method : Total antioxidant capacity (TAC), Total antioxidant response (TAR), Total phenolic content, Reactive oxygen species (ROS), 1,1-Diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging activities, lipid peroxidation were examined. Result : Total antioxidant status was examined by total antioxidant capacity(TAC) and total antioxidant response(TAR) against potent free radical reactions. TAC and TAR of Puerariae Radix extract at the concentration of 5 mg/㎖ were 2.02 and 1.50 mM Trolox equivalents, respectively. Total phenolic content of Puerariae Radix extract at the concentration of 5mg/㎖ was 2.29 mM gallic acid equivalent. Concentration of Puerariae Radix extract at which DPPH radical scavenging activity was inhibited by 50% was 5.91 mg/㎖ as compared to 100% by pyrogallol solution as a reference. The inhibitory effect of the extract on lipid peroxidation was examined using rat liver mitochondria induced by FeSO4/ascorbic acid. Puerariae Radix extract at the concentration of 1 mg/㎖ slightly but significantly decreased TBARS concentration. The extract further prevented lipid peroxidation in a dose-dependent manner. The effect of Puerariae Radix extract on reactive oxygen species (ROS) generation was examined using cell-free system induced by hydrogen peroxide/FeSO4. Addition of 1 mg/㎖ of Puerariae Radix extract significantly reduced dichloroflurescein (DCF) fluorescence. The extract caused concentration-dependent attenuation of the increase in DCF fluorescence, indicating that the extract significantly prevented ROS generation in vitro. Thus antioxidant effects of Puerariae Radix extract seem to be due to, at least in part, the prevention from free radicals-induced oxidation, followed by inhibition of lipid peroxidation. Conclusion : As a result, Puerariae Radix seems to have antioxitative effect and antioxidant compount.